2017
DOI: 10.3892/ol.2017.5757
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of proteins associated with the cytoskeleton by hepatitis B virus X protein during hepatocarcinogenesis

Abstract: Abstract. Hepatocellular carcinoma (HCC) is a major malignant disease worldwide, and chronic hepatitis B virus (HBV) infection is one of the primary causes for this type of cancer. Hepatitis B virus X protein (HBx) is a non-structural protein encoded by the viral genome that has significant effects on the pathogenesis of HCC. With the development of high-throughput assays and technologies, the abnormal HBx-induced expression of certain cellular proteins with assorted biological functions has been investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…In addition, HBx stabilizes amplified in breast cancer 1 (AIB1) protein through preventing it from proteasome-dependent degradation and cooperates with this molecule to enhance the invasiveness of HCC cells [90]. β-catenin is a critical molecule associated with epithelial-mesenchymal transition (EMT) [91], a process that contributes to the invasion of HCC cells. However, the mechanism of β-catenin upregulation in HBV-related HCC is unclear.…”
Section: Main Textmentioning
confidence: 99%
“…In addition, HBx stabilizes amplified in breast cancer 1 (AIB1) protein through preventing it from proteasome-dependent degradation and cooperates with this molecule to enhance the invasiveness of HCC cells [90]. β-catenin is a critical molecule associated with epithelial-mesenchymal transition (EMT) [91], a process that contributes to the invasion of HCC cells. However, the mechanism of β-catenin upregulation in HBV-related HCC is unclear.…”
Section: Main Textmentioning
confidence: 99%
“…HBV possesses four overlapping open reading frames, namely C, P, S and X (2426). The coding protein HBX was reported to possess multiple transcriptional regulatory activities (2,30,31). The present study explored whether HBX alone could facilitate AP1M1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies have demonstrated that HBV infection can increase the risk of liver cancer, the exact molecular mechanism of this process remains undiscovered (1,2,5,6). In the present study, it was demonstrated that AP1M1 acted as a cancer-promoting factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial-mesenchymal transition (EMT) is a significant event in the development of HBV-associated HCC [ 7 ]. HBX has been reported to induce the EMT phenotype in hepatoma cells [ 8 11 ], with the decreased levels of epithelial cell–cell adhesion molecule E-cadherin, while the increased expressions of cytoskeletal actin component β-catenin and vimentin. Moreover, HBX can regulate the expression of E-cadherin and β-catenin with multiple molecular mechanisms [ 11 ].…”
Section: Introductionmentioning
confidence: 99%